Practical activities in laboratory spaces in the teaching of Science and Biology: reports of an experience with students in the final years of basic education in Ilha de São Luís – MA (Research, Society and Development, 2021)
Laboratories are spaces of construction of a good part of biological scientific knowledge. When used in teaching, they offer opportunities to bring basic education students closer to scientific production, awakening interest in science in young people. In this work we aimed to approach the students of the final years of basic education to the Warwick Kerr Genetics and Molecular Biology Laboratory (LABWICK) of the Universidade Estadual do Maranhão and investigate the perceptions of these students about practical laboratory activities in science and biology classes. To this end, the work had three phases: diagnosis of the laboratory experiences of students at their school, visit to the, diagnosis of learning during the visit. The initial diagnosis was carried out in 12 schools located on the island of São Luís -MA, and was carried out through the application of a questionnaire (199 students) and on-site observation. During the visits to LABWICK, 9 schools participated in lectures and practical classes. All students who participated in the visit (226) answered the learning diagnostic questionnaire. It was observed the interest and assimilation of content by students in the laboratory environment, as well as reports on the absence of this type of activity within the school environment. Such observations point to the need to expand the use of laboratory spaces in the search for dynamic and interesting science classes.